2014
DOI: 10.1080/01496395.2014.943769
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Alkali Extraction of Triterpene Acids from Poria and Preparative Separation by High-Speed Counter-Current Chromatography

Abstract: A method for the acid-alkali extraction and preparative separation of triterpene acids from poria was established. The triterpene acids were enriched and separated into two fractions after extraction at the optimized pH value. The two fractions were subjected to high-speed counter-current chromatography for the preparative separation of triterpene acids, separately. As a result, dehydropachymic acid, pachymic acid, 3-epi-dehydropachymic acid, poricoic acid B, dehydrotumulosic acid, and 3-epi-dehydrotumulosic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The 1 H- and 13 C-NMR spectra revealed H-11 (δ 5.21)/C-11 (δ 120.7), H-7 (δ 5.17)/C-7 (δ 119.0), C-9 (δ 138.3), C-8 (δ 142.3), H-18 (δ 0.99), H-19 (δ 0.93), H-26 (δ 1.50), H-27 (δ 1.58), H-29 (δ 1.68), H-30 (δ 1.50), H-16 (δ 4.54), H-28 (δ 4.67, 4.76), H-24 (δ 5.27), C-3 (δ 178.3), C-21 (δ 180.0). Based on the structural features of triterpene compounds and the data given in the literature, compound- 1 was identified as poricoic acid B [ 1 , 17 , 20 , 22 , 23 , 24 ]. Poricoic acid B belongs to the 3,4-seco-lanostan-7,9(11)-diene type triterpenes [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H- and 13 C-NMR spectra revealed H-11 (δ 5.21)/C-11 (δ 120.7), H-7 (δ 5.17)/C-7 (δ 119.0), C-9 (δ 138.3), C-8 (δ 142.3), H-18 (δ 0.99), H-19 (δ 0.93), H-26 (δ 1.50), H-27 (δ 1.58), H-29 (δ 1.68), H-30 (δ 1.50), H-16 (δ 4.54), H-28 (δ 4.67, 4.76), H-24 (δ 5.27), C-3 (δ 178.3), C-21 (δ 180.0). Based on the structural features of triterpene compounds and the data given in the literature, compound- 1 was identified as poricoic acid B [ 1 , 17 , 20 , 22 , 23 , 24 ]. Poricoic acid B belongs to the 3,4-seco-lanostan-7,9(11)-diene type triterpenes [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the five triterpenes obtained in the experiment, the open-loop structure had a more significant inhibitory effect on cells than the closed-loop structure. The hydroxyl group at the C16 position can increase the toxicity of triterpenes to tumor cells [24]. Studies have also shown that double bonds in the B and C rings could increase cytotoxicity [6].…”
Section: Antiproliferative Activity Of Paa and Pab On Human Cancer Cellsmentioning
confidence: 99%